PERAN MANAJEMEN PEMBELAJARAN BERDIFERENSIASI DALAM PENGEMBANGAN KOMPETENSI GURU - Putri, Eka Zulia; Karwanto, Karwanto; Haq, Mohammad Syahidul (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to analyze the strategic role of differentiated learning management in developing teacher competencies. Employing a literature review methodology, this study examines and synthesizes various relevant scholarly sources addressing the concept of differentiated learning management and its connection with enhancing teachers' competencies. The findings reveal that the implementation of differentiated learning management—encompassing planning, organizing, implementing, and evaluating learning focused on meeting diverse student needs (through differentiation of content, process, and product based on readiness, interests, and learning profiles)—significantly challenges and sharpens teachers' pedagogical and professional competencies. This process encourages teachers to be more innovative in instructional design, effective in managing heterogeneous classrooms, and adaptive to curriculum demands. It is concluded that differentiated learning management is a crucial and effective approach for the sustainable improvement of teachers' competencies, thus fostering an inclusive and high-quality learning environment.